Valentim Fernandes et ses compilations de récits de voyages (1502-1510) - Rui Manuel Loureiro (Viatica)
Valentim Fernandes, also known as Valentinus Moravus, settled in Portugal in the early 1490s. A few years later, he was already closely linked to the Portuguese Royal House and had become the most important printer operating in Portugal. In addition to publishing a wide range of works of a religious, legal, and humanist nature, he gathered two important collections of travel reports. One of them was printed in 1502 in Lisbon under the title Marco Paulo; the other, which remained in manuscript and was eventually integrated into the library of the German statesman Konrad Peutinger, is known as Codex Valentim Fernandes. This article aims to bring to light and make known these two compilations as well as the context of their constitution.